Fluorescence cystoscopy in patients with non-muscle invasive bladder cancer - I. G. Rusakov; A. A. Teplov; R. V. Ulianov; E. V. Filonenko (Biomedical Photonics)
The main challenge of treating non-muscle invasive bladder cancer is multifocal tumors. Current methods of diagnosis are failed to detect all superficial flat tumor lesions in bladder mucosa. The use of fluorescence imaging with 5-aminolevulinic acid (5-ALA) allows to improve the sensibility of routine cystoscopy, but low specificity decreases its diagnostic accuracy. The method of fluorescence imaging combined with local fluorescence spectroscopy developed in P.A. Herzen MCRI has been shown to increase the specificity from 71% to 84%. Thus, local fluorescence spectroscopy in visible fluorescence of 5-ALA-induced protoporphyrin allows to perform guided biopsy and decrease the rate of diagnostic mistakes.